MULTI-OBJECTIVE OPTIMIZATION OF A VEHICLE’S DYNAMIC RESPONSE TO EXCITATIONS CAUSED BY A ROAD PROFILE THROUGH A META-HEURISTIC ALGORITHM - Fossati, Giovani G.; Miguel, Letícia F. F. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The proposed work uses a meta-heuristic algorithm with a multi-objective approach to optimize the suspension parameters of a half car ride model, representing a passenger car, when it travels at a constant speed on a certain road profile. The numerical-computational routine developed seeks to simulate the dynamic behavior of the vehicle model in response to the excitations caused by the pavement’s irregularities, and to obtain the parameters that minimize both the vertical acceleration of the driver seat and the front and rear tire deflections of the model. The ISO 8608 (1995) standard methodology is used to obtain the base excitation signals that represent the track’s irregularities. The method proposed by Shinozuka and Jan (1972) is used to obtain the road irregularity profile in the time domain from the power spectral density (PSD) equations that represent the different pavement classes. The Newmark’s method (1959) is used to solve the differential motion equation in order to obtain the vehicle model’s responses to these irregularities. Finally, the NSGA-II meta-heuristic algorithm proposed by Deb et al. (2002) is used to obtain the optimal suspension parameters, which minimize the vertical accelerations of the driver seat.